POTENTIALITY OF MODERN ULTRASOUND EVALUATION OF LIVER STRUCTURE BY THE EXAMPLE OF GILBERT'S SYNDROME - M.I. Pykov; I.N. Zakharova; Z.V. Kaloeva (Union of pediatricians of Russia, 2011)
Technical advances in recent years have greatly expanded the diagnostic potentialities of ultrasound study, providing opportunities in a number of cases to diagnose and begin treatment as soon as possible. The authors propose to use the method of assessment of the liver parenchyma using acoustic histometry. We examined 200 children aged 8 to 16 years with a preliminary diagnosis of Gilbert's syndrome. We studied gene UGT1A1 in all children, performed an ultrasound scan of the liver and spleen, and calculated the liver-spleen index. Two examples using the new method of noninvasive diagnosis have been cited. The obtained results of the study demonstrate the high sensitivity and specificity of this technique, and can be recommended in addition to the traditional ultrasound scan. Key words: liver, spleen, Gilbert's syndrome, ultrasound, acoustic histometries, liver-spleen index, children. (Pediatric Pharmacology. - 2011; 8 (5): 88-90.)